Evaluación de rentabilidad de la certificación orgánica del café en la provincia de Loja - Espinosa Romero, María José (2015)
The main objective of this research was to evaluate the profitability of organic coffee certification in the province of Loja by comparing the costs and benefits of certified organic production versus traditional production. Financial indicators such as NPV, IRR and Kilian equation allowed determining whether an economic benefit to farmers who have organic certification is certain. Traditional coffee production obtained higher IRR compared to certified production; however the NPV was higher for certified organic production, so as these two mutually exclusive projects calculating the IRR would not matter so the production of certified coffee would be taken as a better option for farmers. In the equation of Kilian a positive value at which the economic benefit of certified organic production is confirmed was obtained.